TEKNIK EDITING DENGAN MENGOPTIMALKAN KONTINUITAS GAMBAR DALAM PRODUKSI FEATURES “BOYOLALI TERSENYUM” - Agustiono, Tri (Jurnal Ilmu Komunikasi AKRAB, 2017)
ABSTRACTBoyolali is a regency located in Central Java Province. Boyolali district is one of the districts with the largest milk producers in Java. Features with a duration of 20 minutes 20 seconds selected so that people who want to know more about information from Boyolali district can be realized. The information presented includes the latest icons from Boyolali, Cattle Farm until Processing of milk to be cheese, Regional Arts and various tourist attractions not yet widely known by many people.To support this feature program to be more interesting and comfortable witnessed by the audience, need good and appropriate editing in accordance with the initial goal of the continuity. With guidelines to optimize the continuity of images in order to obtain continuity of the image, embodied with cutting, transition, coloring, masking, titling and time-lapse techniques in these Boyolali Tersenyum features found in each sequence and scene. Coupled with the backsound alignment in accordance with the mood of the picture and the script read by the narrator who increasingly invites the audience to understand the information.This Boyolali Tersenyum features produce an audio visual works an interesting, informative and able to give its own impression to the audience. Can be useful and can be an inspiration and reference for the wider community who have witnessed this work of Features.Keywords : Editing, Continuity, Features, Boyolali